1888 Md. Code 522-23 - (:unkn) unknown (My University, 1884)
Ch. 187, § 742: Prohibited the carrying of a pistol, dirk knife, Bowie knife, slingshot, billy, brass, iron or any other metal knuckles, razor, or any other deadly weapon if arrested for being drunk and disorderly. Punishable by fine of $5-25, and confiscation of the weapon.
Keywords: CARRY; CARRY - CONCEALED - DANGEROUS PERSONS; POSSESSION - DANGEROUS PERSONS